Experimental Platform for Studying Hardware Vulnerabilities on Mobile Robots: I2C Bus, a Case of Study. - F. Gómez Bravo; J. Medina García; R. Jiménez Naharro; J.A. Gómez Galán; M. Sánchez Raya (Revista Iberoamericana de Automática e Informática Industrial RIAI)
This paper presents an experimental platform for studying the effects of hardware vulnerabilities in mobile robots. The platform is designed so that the hardware, involved in the navigation process, can be monitored during the robot operation and, if desired, their behavior can be altered, allowing the simulation of a failure. The paper shows a particular case of study: the I2C Bus vulnerability when some anomalies appear in the clock signal. A set of experimental results confirm the interest of the studied vulnerabilities and the applicability of the developed platform.